Geological Study of Unusual Tsunami Deposits in the Kuril Subduction Zone for Mitigation of Tsunami Disasters - Nanayama, Futoshi; Shigeno, Kiyuyuki; Shitaoka, Yorinao; Furukawa, Ryuta (IntechOpen, 2011)
None